Ataques de Nervios and Somatic Complaints Among Island and Mainland Puerto Rican Children - Lopez, Irene (CNS Neurosci Ther, 2010)
Previous research has documented the association between the Latino cultural idiom of distress, ataques de nervios (i.e., “attacks of nerves”), and unexplained neurological symptoms among adults. However, the associations between ataques and somatic complaints in children have not been sufficiently explored. Aims: In this study, we assessed the relation between this anxiety‐related experience, henceforth ataques, and somatic complaints in a probability sample of Puerto Rican youth, ages 5–13 years, living in San Juan, Puerto Rico (N = 1353) and in the South Bronx, New York (N = 1138). When both sites were combined, children with ataques were significantly more likely to have either a lifetime prevalence of asthma or headaches, and tended to have more stomach aches and a history of epilepsy or seizure than children without ataques. Further within site analyses showed a similar patterning of complaints for the South Bronx sample as for the combined sample. However, children in San Juan with ataques were only slightly more likely to experience headaches, and at risk for injury, than those without ataques. In addition, comparisons between ataque sufferers across sites indicated that children in San Juan with ataques were at elevated risk for serious illness or injury in comparison to those in the South Bronx with ataques. Ataques are significantly associated with a wide range of physical complaints in Puerto Rican youth. However, their pattern of associations differs by context.